Desenvolvimento da antera e dos grãos de pólen em Adenium obesum - Deborah Cristina Dias Campos (2021)
Adenium obesum (Forssk.) Roem. & Schult., popularly known as desert rose, is a plant with great landscape potential, whose propagation by seeds is the desirable way for the formation of voluminous caudex. Reproductive processes, including microsporogenesis and microgametogenesis, are essential for seed production. The objective of this work was to study the development of anthers identifying the main stages of microsporogenesis and microgametogenesis and characterizing the pollen grains in the dispersal phase from cultivated plants of A. obesum belonging to an access characterized by simple corolla and with pink coloration. Flower buds and flowers at different stages of development were collected and processed according to usual plant anatomy protocols. Additionally, pre-anthesis flower bud pollen grains were submitted to histochemical tests to identify starch and lipids. The anthers of A. obesum are biteca and with longitudinal dehiscence, have a triangular shape, sagittal base and pinkish filamentous appendages in the apical region. In cross-section, anthers are tetralobed, covered by the epidermis, endothelium, middle layers and mat. Cenective region with isodiametric cells with peripheral cytoplasm, developed vacuoma and evident nuclei, in addition to a vascular bundle in a central position. During development (0.68 cm – phase 3), it is possible to observe the formation of a groove in the septum region between the microsporangia of the same theca, corresponding to the stomatal region. The cells that make up the parietal strata undergo transformations as the anthers mature. Microsporogenesis was terminated when the bud reached about 0.5 cm. Buttons starting at 1.44 cm, the immature microsporotic acquires a circular shape. Pollen grains are bicellular, contain amylaceous reserve and are dispersed in monads, joined by lipids. Based on the data obtained from the present work, we can conclude: the anther wall has five parental strata, epidermis, endothelium, secretory-type mat and two middle layers. Cytokinesis is simultaneous type and tetrahedrals are tetrahedral.